2007
DOI: 10.1194/jlr.m700077-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosylphosphorylcholine acts in an anti-inflammatory manner in renal mesangial cells by reducing interleukin-1β-induced prostaglandin E2 formation

Abstract: Sphingosylphosphorylcholine (SPC) is a bioactive lipid that binds to G protein-coupled-receptors and activates various signaling cascades. Here, we show that in renal mesangial cells, SPC not only activates various protein kinase cascades but also activates Smad proteins, which are classical members of the transforming growth factor-b (TGFb) signaling pathway. Consequently, SPC is able to mimic TGFbmediated cell responses, such as an anti-inflammatory and a profibrotic response. Interleukin-1b-stimulated prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…42,43 Another study showed that SPC activates the transforming growth factor b/Smad signaling cascade and, thereby, is able to reduce the promoter activity and expression of pro-inflammatory enzymes like secretory phospholipase A2 and iNOS in renal mesangial cells. 44 SPC is probably due to its activity in reducing iNOS to keep NO levels within physiological limits. Positive effects of SPC kept NO levels in physiologic limits so that vascular permeability is kept within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Another study showed that SPC activates the transforming growth factor b/Smad signaling cascade and, thereby, is able to reduce the promoter activity and expression of pro-inflammatory enzymes like secretory phospholipase A2 and iNOS in renal mesangial cells. 44 SPC is probably due to its activity in reducing iNOS to keep NO levels within physiological limits. Positive effects of SPC kept NO levels in physiologic limits so that vascular permeability is kept within normal limits.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosylphosphorylcholine exerts most of its action by binding to and activating cell surface receptors, thereby triggering various cell responses such as vasoconstriction or dilation, angiogenesis, stress fiber formation, and cytoskeletal rearrangements [37,38]. Another study showed that SPC activates the transforming growth factor β/Smad signaling cascade and, thereby, is able to reduce the promoter activity and expression of pro-inflammatory enzymes like secretory phospholipase A2 and iNOS in renal mesangial cells [39]. In the present study, SPC reduced pulmonary injury owing to pulmonary contusion through its anti-inflammatory effect.…”
Section: Controlmentioning
confidence: 96%
“…Cardiac hypertrophy at a cell level can be characterized by an increase in cell size or protein to cell in cardiac myocyte area (24,31). Recent studies have identified markers of pathological cardiac hypertrophy, with "fetalization" of the cardiac myocytes and expression of genes such atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), ␣-skeletal actin (␣-SKA), and ␤-myosin heavy chain (␤-MHC) (4,20,35,53).…”
mentioning
confidence: 99%